Sociodemographic Characteristics as Predictors of Climate Change Anxiety among Adults in Flood Affected Areas of Pakistan - Zareen, Sabahat; Akhtar, Tanvir; Zaman, Sabir (Annals of Human and Social Sciences, 2024)
The primary objective of this study was to assess the cognitive, emotional, and functional impairment as well as the psychological well-being of adults. Natural disasters are reoccurring in Pakistan and the mental health consequences of these floods need attention of researchers. The sample of the study included 350 adults, consisting 173 men and 177 women. Climate change anxiety scale along with a demographic questionnaire were used for data collection and all ethics were followed. The findings indicated that climate change affect the cognitive, emotional, and functional abilities of Adults, ranging from mild stress to severe clinical conditions like anxiety. Women showed high levels of climate change anxiety then men. Moreover, individuals with higher education levels generally reported lower anxiety levels than those with lower education levels. Addressing the mental health needs of these vulnerable populations would be a priority for organizations and mental health researchers.